Hubungan Pola Asuh Orang Tua dan Lingkungan Sosial dengan Perilaku Seksual Remaja Usia 14–21 Tahun di Lingkungan Lokalisasi - Ah. Yusuf; Khoridatul Bahiyah; Hanik Endang Nihayati; Agung Tri Wiyono (Universitas Airlangga, 2007)
Introduction: The objective of this study was to examine the correlation between parenting and social environtment with sexual behavior for adolescence (14–21 years) who lived in Putat Jaya prostitution area Surabaya.Methods:Design used in this study was cross sectional design. The population were all adolescence who lived around in Putat Jaya prostitution area Surabaya. Total sample were 104 respondents, taken according to inclusion criteria. The independen variables were parenting and social environtment and the dependent variable was sexual behavior in adolescence (14–21 years). Data were collected by using structured questionaires with multiple choice and several open questions. Data were then analyzed by using Spearman’s Rho Correlation with level of significance p=0.05 and content analyse.Result : showed that parenting had a strong correlation with sexual behavior in adolescence (p=0.000 and ρ=0.691) and the social environtment had a strong correlation with sexual behavior in adolescence (p=0.000 and ρ= –0.773). Conclusion: parenting and social environtment has correlation with sexual behavior in adolescence and the most factors that have strong relationship in those correlations is living in prostitution area nearby. It is recommended for nurse, parent and publics to modified the social environtment to be more condusiveness. The Benefit of Family Nursing Care in Improve Knowledge and Prevent the Deformity of Leprosy Patient